Abnormal Return and Trading Volume Activity Before and After Presidential Election 2019 ( Study on LQ-45 stock on February-July 2019) - C H Asta Nugraha; Suroto Suroto (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2019)
This study aims to find out the empirical evidence of Indonesia capital market investorsâ€™ reaction toward presidential election 2019. The population in this study is the companiesâ€™ stocks which are included in the LQ-45 index during this study. The data used is secondary data in the form of LQ-45 stocks and daily Composite index three days before and three days after the event. By implementing the one sample t-test and paired samples t-test, the result shows that there is a positive and significant abnormal return around the event especially on the third day (t+3) after the event.Â Moreover, there is an insignificant difference in the average of negative abnormal return and significant difference on the average of negative trading volume activity, before and after the presidential election 2019.